Rite of feeding food in the Qur’an and Sunnah, its virtues and images - Yahya, Mohammad (Jordan Journal of Islamic Studies, 2023)
This research deals with the study of a topic that is considered one of the main pillars in achieving social solidarity in the Islamic society, which is feeding food in the Qur’an and Sunnah. The light on the reality of this ritual and the statement of its many virtues, the most important of which is escaping from Hellfire and entering Paradise. The scientific method from its sources, as well as the analytical method based on analyzing the scientific material and extracting judgment and rulings from it. The research concluded with a number of results, the most important of which is the contribution of this ritual to achieving food security for all people at all levels, in addition to consolidating the meanings of spoilage, mercy and love among them.